Emotion and its Management: The Lens of Language and Social Psychology. (January 2021) - Gallois, Cindy; Vanman, Eric J.; Kalokerinos, Elise K.; Greenaway, Katharine H.
In this paper, we briefly review the large research literature on emotion in social psychology, and show how it is now firmly embedded in language and communication. As a springboard, we look at the history of emotion studies in JLSP . Then, we consider theory and methodology, and evaluate how standard and more recent methods of measurement have led to new ways of looking at the communication of emotion, including in real-life contexts. We conclude with suggestions for a research agenda that takes the study of emotion forward into the heartland of research in language and social psychology.